Effectiveness assessment of adapted business processes in the context of digital transformation - Shytikova, Larisa; Pulina, Tеtiana; Yaroshenko , Oleksii (Management and Entrepreneurship: Trends of Development, 2025)
The article explores the theoretical and methodological principles of assessing the effectiveness of business processes of organizations in the context of digital transformation. The proposed research topic allows us to assert that assessing the real effectiveness of adapted business processes in the context of digital transformation is a complex multi-level task, since it covers various aspects of the organization's activities: economic, informational, technological, financial, organizational and socialThe article determines that digitalization creates a new management paradigm, in which data, analytics and technological innovations become the key resource. It is substantiated that traditional financial indicators do not fully reflect the real impact of digital changes on the organization, since the effectiveness of digital processes is multidimensional. A systematic approach to assessing the effectiveness of adapted business processes is proposed, which combines quantitative and qualitative methods of analysis. Using the specifics of the system approach, it is possible to study the patterns, methods and techniques of forming complex objects, which are the business processes of organizations in the context of digital transformation.The article determines that the implementation of the set goal will contribute to the formation of a comprehensive approach to measuring the efficiency of business processes, will provide the possibility of operational management of digital transformations and will increase the competitiveness of organizations in the digital economy. It is proved that to ensure the objectivity of the results of the efficiency assessment, it is necessary to use combined approaches that combine quantitative and qualitative methods; the consequence of such a synergistic approach is the formation of a more complete picture of the efficiency of transformational changes. It is noted that it is advisable to use an integral indicator of the efficiency of digital transformation, which is based on the weighting coefficients of the significance of individual indicators. The article substantiates the need to include in the assessment not only economic, but also organizational, social and technological aspects that reflect the level of adaptability and digital maturity of the organization. It is determined that the efficiency of digital transformation should be assessed as a continuous process integrated into the strategic management system that ensures sustainable development and competitiveness of organizations.JEL Classification: M15, O33, D24, L86, M11